KESALAHAN UMUM DALAM PERUMUSAN MASALAH PENELITIAN PENDIDIKAN DAN CARA MENGHINDARINYA - Muhammad Ariq Musthofa; Ghina Zahidatushalihah Firdausi; Alifia Hasya Nadhira; Salma Humairah; Putri Novita Sahri; Ahman (CV. ADIBA AISHA AMIRA, 2025)
Problem formulation is a fundamental component in educational research because it determines the overall direction and focus of the study. However, many researchers—particularly students and education practitioners—often make mistakes in formulating research problems, such as being too general, non-operational, and irrelevant to the research context. These errors directly affect the quality of the methodology, the validity of the results, and the effectiveness of the research in addressing real educational issues. This study aims to identify common types of mistakes in problem formulation and to offer concrete strategies to avoid them. The approach used in this research is qualitative, employing a literature review method. The findings of this study include overly general problem statements, problems that are not based on theoretical review and preliminary data, problem statements that are inconsistent with the research objectives and methods, and problems that are difficult to measure.